Molecular Dynamics Simulation on Tensile Behavior of Cellulose at Different Strain Rates - Kaixiang Jiang; Zhe Yan; Wenjuan Fang; Youqiang Zhang (Advances in Materials Science and Engineering)
At present, most high-performance cellulose matrix composites only use cellulose as reinforcement material, which is an obstacle to maximize the advantages of nanocellulose in structure and properties. The development of new functional nanocomposites with cellulose as the main component can better meet people’s needs for high-performance and degradable composites, which requires a comprehensive and thorough understanding of cellulose. Considering the limitations of physical experiments, we performed molecular dynamics simulation of the uniaxial tensile behavior of the cellulose system at three different strain rates (10−4/ps, 10−5/ps, and 10−6/ps), and the stress-strain responses of cellulose systems at different strain rates are obtained. The effect of the strain rate on the mechanical properties of amorphous cellulose system during the tensile processes is analyzed. The deformation mechanism of cellulose amorphous system during the tensile processes is characterized by the energy changes of the different terms including dihedral angle torsion term, bond tensile term, angle bending term, and nonbond term. Structural evolution of the cellulose crystal system during the tensile processes is used to explain the failure mechanism of cellulose. The kinetic simulation results show that the mechanical properties of the cellulose amorphous system increase with the increase of strain rate. Compared with the strain rate of 10−5/ps, the elastic modulus of the system increases by 6.73 GPa at the strain rate 10−4/ps. During the tensile processes, cellulose amorphous region adapts to the applied load mainly through the stretching of the cellulose macromolecular chains, i.e., the deformation of bond lengths and bond angles, without any breakage of the molecular chains. The main causes of chain lengthening at different strain rates are different. The failure of cellulose is caused by the slip and rearrangement of some molecular chains in the crystal structure.